2018
DOI: 10.25300/misq/2018/13245
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Technology Infrastructure Flexibility on Mergers and Acquisitions

Abstract: Although mergers and acquisitions (M&A) are a common strategy to reduce costs and pursue growth, the variance in returns from M&A is very high. This research examines how information technology (IT) infrastructure flexibility affects M&A. We use a combination of secondary as well as matched-pair survey data from 100 midsize firms in Spain to investigate this relationship. The empirical analysis suggests that IT infrastructure flexibility affects M&A through two key pathways: (1) a flexible IT infrastructure fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 76 publications
1
155
1
3
Order By: Relevance
“…We found that the significance obtained from both models remained the same, indicating that endogeneity bias is not a potential threat to our results. From these results, we conclude that our error terms are orthogonal, which means that the model cannot be reversed (Benitez et al, 2018).…”
Section: Additional Analysesmentioning
confidence: 85%
“…We found that the significance obtained from both models remained the same, indicating that endogeneity bias is not a potential threat to our results. From these results, we conclude that our error terms are orthogonal, which means that the model cannot be reversed (Benitez et al, 2018).…”
Section: Additional Analysesmentioning
confidence: 85%
“…Assessing the path coefficients of the cross-sectional data set (Table 10), we found that the path coefficients BPMC -> PP and M -> BPMC had low p-values, were reasonably large, and in the expected directionality. The data on the relation between M and PP might signify that BPMC does not fully mediate the linkage between M and PP in the overall cross-sectional data set, so we performed a mediation analysis to better understand how far BPM culture mediates between BPM methods and process performance (Benitez, Ray, & Henseler, 2018;Preacher & Hayes, 2004;Zhao, Lynch Jr., & Chen, 2010). We used bootstrapping to assess mediation.…”
Section: Figure 2 Structural Model Results With Estimates From the Crmentioning
confidence: 99%
“…Researchers predominantly apply PLS to obtain construct scores or inter-construct correlations that can be used in follow-up analyses. For instance, Benitez et al (2018) use covariance-based structural equation modeling to estimate a nonrecursive structural model using an inter-construct correlation matrix obtained through PLS. PLS construct scores play a pivotal role in two-step procedures for estimating moderating effects (see, e.g., Dijkstra and Schermelleh-Engel 2014;Fassott et al 2016;Henseler and Fassott 2010), non-linear effects (see, e.g., Henseler et al 2012), and higherorder constructs (see, e.g., van Riel et al 2017).…”
Section: Pls Is a Suitable Technique For Descriptive Purposes If The mentioning
confidence: 99%